2006
DOI: 10.1080/00365540500361302
|View full text |Cite
|
Sign up to set email alerts
|

Important differences in components of the metabolic syndrome between HIV-patients with and without highly active antiretroviral therapy and healthy controls

Abstract: The aim of this study was to compare the prevalence of metabolic syndrome and insulin resistance in HIV-positive patients with and without HAART and healthy HIV-negative controls. In total 357 subjects were examined: 56 HIV-positive HAART-naïve, 207 HIV-positive on HAART treatment and 94 HIV-negative controls. We measured blood pressure, abdominal circumference, weight and height, and fasting serum levels of glucose, insulin and lipids in all the subjects. The presence of lipodystrophy was assessed in the HAAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…The prevalence of MS in our cohort was high (27%) compared with the prevalences reported in other studies of HIV-infected patients, which have ranged from 16 to 24% [2,5,[7][8][9][10], with identical definitions of MS being used. Our cohort had a similar distribution with regard to sex, age, body mass index (BMI), blood pressure, known duration of HIV infection and duration of HAART compared with a range of previous studies determining the prevalence of MS in HIV-infected patients [2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The prevalence of MS in our cohort was high (27%) compared with the prevalences reported in other studies of HIV-infected patients, which have ranged from 16 to 24% [2,5,[7][8][9][10], with identical definitions of MS being used. Our cohort had a similar distribution with regard to sex, age, body mass index (BMI), blood pressure, known duration of HIV infection and duration of HAART compared with a range of previous studies determining the prevalence of MS in HIV-infected patients [2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 63%
“…However, selection bias and small study populations have hampered these prevalence studies. The influence of highly active antiretroviral therapy (HAART) on the development of MS is still a matter of controversy, but a higher prevalence of MS in HIV-infected patients on HAART compared with the background population has been proposed [7,9]. An Correspondence: Dr Birgitte R. Hansen, Clinical Research Centre, Copenhagen University Hospital, Hvidovre, Kettegaard Allé 30, DK-2650 Hvidovre, Denmark.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective studies found a higher prevalence of MS associated with HAART use [3,[13][14][15][16] and in particular with PIs, [2,3,14,16] whereas others did not find any association [4,12,17,18]. Some authors suggested that HAART specifically affected the triglycerides levels [5,19,20] and the insuline resistance [13]. Specific antiretroviral therapies are known to affect individual components of MS adversely, such as increasing triglycerides as lopinavir/ritonavir, [21,22] but also efavirenz [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is usually known that lipodystrophy is associated with other metabolic abnormalities, only a portion of patients with lipodystrophy have other metabolic complications, while some HIV-infected subjects receiving HAART have metabolic syndrome and/or insulin resistance without having lipodystrophy (Chen et al 2002;Bergersen et al 2006;Wierzbicki et al 2008). Therefore, it may be postulated that metabolic abnormalities occurred before the obvious development of lipoatrophy in some patients (Chen et al 2002).…”
Section: Discussionmentioning
confidence: 99%